2012
DOI: 10.3109/09537104.2012.704648
|View full text |Cite
|
Sign up to set email alerts
|

Effects on platelet function of an EP3 receptor antagonist used alone and in combination with a P2Y12antagonist bothin-vitroandex-vivoin human volunteers

Abstract: EP3 receptor antagonists may provide a new approach to the treatment of atherothrombotic disease by blocking the ability of prostaglandin E2 (PGE2) to promote platelet function acting via EP3 receptors. DG-041 is an EP3 antagonist in the early stage of clinical development. Here, we quantitated effects on platelet function of DG-041 in-vitro and ex-vivo after administration to man when given alone and concomitantly with clopidogrel or clopidogrel and aspirin. With its unique mechanism of action, it was anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…Our in vitro findings that EP3 receptor stimulation enhanced washed platelet aggregation and adhesion are in line with previous findings, showing an EP3-induced increase of agonist-induced aggregation in human whole blood and PRP [18,21,25] . In addition, we found that adhesion to fibrinogen and collagen under low flow conditions is enhanced based on EP3 receptor activation; however, whole blood thrombus formation on collagen under high flow was not significantly affected by the EP3 receptor agonist sulprostone.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our in vitro findings that EP3 receptor stimulation enhanced washed platelet aggregation and adhesion are in line with previous findings, showing an EP3-induced increase of agonist-induced aggregation in human whole blood and PRP [18,21,25] . In addition, we found that adhesion to fibrinogen and collagen under low flow conditions is enhanced based on EP3 receptor activation; however, whole blood thrombus formation on collagen under high flow was not significantly affected by the EP3 receptor agonist sulprostone.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the ex vivo experiments showed that DG-041 enhanced the effect of P2Y 12 antagonist clopidogrel [21] . Most remarkably, in contrast to P2Y 12 antagonists, DG-041 does not increase bleeding time in man, rat and mice [21][22][23] . Atherothrombosis is a leading cause of death, and anti-platelet drugs improve the survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a phase I trial did not show any impact on bleeding time in volunteers [22,35] who received high doses of the EP3 blocker DG-041. The maximal tested dose reached 8 times the dose needed to fully inhibit the in vitro potentiating effect of PGE2 on human platelets.…”
Section: Does the Platelet Ep3 Paradigm Apply To Human Platelets?mentioning
confidence: 91%
“…The circumstance was a clinical trial in which a new antiplatelet agent, an EP3 receptor antagonist, was administered to volunteers with and without clopidogrel or clopidogrel and aspirin, after which the effectiveness of the drugs as inhibitors of platelet aggregation was assessed [46]. More recently, AGGFix has also been used successfully for assessment of platelet aggregation using the platelet counting approach in blood placed in 96-well plates and also, in parallel, to assess the degree of platelet-leukocyte conjugate formation that occurred, assessed by flow cytometry [47].…”
Section: Platelet Countingmentioning
confidence: 99%